Beyond the Notes: Journeys with Chamber Music - Tomes, Susan (Woodbridge The Boydell Press, 2004)
'Beyond the Notes' is a collection of writings which started as my private diary about the life of the chamber group Domus in the early 1980s. Domus was named after the portable concert hall, in the form of a geodesic dome, which a group of young idealistic musicians took around and put up in places where it was not usually possible to hear concerts. For several years we travelled with our dome to fields, hilltops, parks and city squares in Europe and Australia. Later we moved into the traditional concert hall, where we continued to develop our thoughts and expertise about the chamber music we loved. Part One of the book gives an insight into our difficulties and achievements when traveling with our dome. Part Two is a collection of my later essays about other aspects of performing and preparing for concerts.
Keywords: Historically informed performance